2019
DOI: 10.1371/journal.pone.0213956
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pterygium on the ocular surface and meibomian glands

Abstract: PurposeTo analyze how ocular surface parameters correlate to presence of pterygium and investigate the possible impact of pterygia on tear film findings and meibomian glands findings.MethodsWe investigated objective parameters of the ocular surface such as conjunctival hyperemia, tear film stability and volume, meibomian gland dysfunction, dry eye disease, corneal topography comparing healthy individuals and correlating with the pterygium clinical presentation.ResultsA total of 83 patients were included. Corne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 21 publications
(23 reference statements)
6
17
0
Order By: Relevance
“…Several studies have discovered an association between meibomian gland dysfunction and pterygium. 6,10,22 One of these studies mentioned that the meibomian gland loss area was predominantly located on the nasal side in eyes with pterygium. 6 This idea is supported by the present investigation examining the correlation between meibomian gland dysfunction and pterygium location.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have discovered an association between meibomian gland dysfunction and pterygium. 6,10,22 One of these studies mentioned that the meibomian gland loss area was predominantly located on the nasal side in eyes with pterygium. 6 This idea is supported by the present investigation examining the correlation between meibomian gland dysfunction and pterygium location.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although several theories such as long-term compression by direct contact or disruption of the microenvironment by inflammatory mediators have been proposed, the pathogenesis of this condition has yet to be determined. 6,10 In the current study, dry eye symptoms, the prevalence and severity of meibomian gland dysfunction, and the relationship between meibomian gland dysfunction and pterygium location were evaluated in patients with pterygium and compared with the results from healthy volunteers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In support of our findings, a prior study argued that pterygium excision has a remarkable astigmatism effect on the posterior surface of cornea, and the effect of astigmatism increased with age and higher preoperative posterior astigmatism [ 19 ]. Pterygium not only causes corneal irregularities, conjunctival congestion, and tear film changes but also has a significant impact on the ocular surface by directly changing the morphology of the meibomian gland, causing visible symptoms and potential signs of dysfunction [ 20 ]. After treatment, BUT and SIT levels in the two groups increased, and the study group was significantly higher than the control group, suggesting that the treatment can effectively improve the symptoms of dry eye and improve the function of the lacrimal gland.…”
Section: Discussionmentioning
confidence: 99%
“…The current study showed higher MGD in pterygium patients in comparison to the controls, which is similar to the previous results. [15][16][17][18] This can be explained on the basis of the notion that the direct contact of pterygium with palpebral conjunctiva squeezes the MGs which leads to alterations in glands. Still, a detailed study is needed to determine the pathological process of MGD and unstable tear film in pterygium patients.…”
Section: Discussionmentioning
confidence: 99%